Should Discretionary Power be Controlled Politically Through the Democratic Process or it Should be Controlled Through the Courts? - Ronald Osei Mensah (Mediterranean Journal of Social Sciences, 2022)
The number one function of governments anywhere in the world is to achieve public interest. Public interest and social interactions are so vast, complex and dynamic that; a government can not effectively administer all aspects by itself. Plainly put, whenever citizens require or request for a service from government, it is an implicit request for government to set up an institution to administer the discharge or provision of that service. Owing to this, institutions are set up to aid in the management of the different facets of public service. These institutions and their officials are then conferred power to effectively perform their functions. This power is Discretionary Power. The paper examines discretionary power from various angles and especially investigates the lingering question of how this power should be controlled to prevent abuse. The standpoint of the author is that judicial control is the most effective means of regulating the use of discretion. Received: 2 August 2022 / Accepted: 27 October 2022 / Published: 5 November 2022